2014
DOI: 10.1128/mbio.02035-14
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus-Encoded pUL7 Is a Novel CEACAM1-Like Molecule Responsible for Promotion of Angiogenesis

Abstract: Persistent human cytomegalovirus (HCMV) infection has been linked to several diseases, including atherosclerosis, transplant vascular sclerosis (TVS), restenosis, and glioblastoma. We have previously shown that factors secreted from HCMV-infected cells induce angiogenesis and that this process is due, at least in part, to increased secretion of interleukin-6 (IL-6). In order to identify the HCMV gene(s) responsible for angiogenesis promotion, we constructed a large panel of replication-competent HCMV recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 44 publications
0
50
0
Order By: Relevance
“…Until now, 3-OS HS has been known to mediate herpes simplex virus (HSV) entry in primary cultures of corneal stroma derived from human eye donors (28). Since 3-OS HS facilitates HCMV infection, its further potential in overall disease development, especially in immune modulation or angiogenesis, can be further investigated using corneal endothelial cells (42). Several lines of evidence already suggest that sulfated HS plays a critical role during multiple pathophysiological processes, including inflammation and vascular angiogenesis (43)(44)(45).…”
Section: Expression Of 3-ost Enzymes In His Cells Enhances Fusion Witmentioning
confidence: 99%
“…Until now, 3-OS HS has been known to mediate herpes simplex virus (HSV) entry in primary cultures of corneal stroma derived from human eye donors (28). Since 3-OS HS facilitates HCMV infection, its further potential in overall disease development, especially in immune modulation or angiogenesis, can be further investigated using corneal endothelial cells (42). Several lines of evidence already suggest that sulfated HS plays a critical role during multiple pathophysiological processes, including inflammation and vascular angiogenesis (43)(44)(45).…”
Section: Expression Of 3-ost Enzymes In His Cells Enhances Fusion Witmentioning
confidence: 99%
“…Although various HCMV proteins increase GBM cell proliferation, invasion, and angiogenesis (20,21), a mechanistic link between HCMV and cancer in vivo has not been established, and the role of HCMV in GBM remains a subject of debate, with some groups unable to detect the presence of CMV in tumor specimens (22,23). The use of mouse models to investigate the role of CMV in tumor growth would therefore be helpful in understanding the potential importance of CMV in GBM as well as providing an opportunity to rationally investigate antiviral therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we showed that, when ectopically expressed, UL7 attenuates the production of tumor necrosis factor alpha (TNF-␣), IL-8, and IL-6 in primary monocyte-derived dendritic cells. Subsequent studies by MacManiman and coworkers (22) have indicated that soluble UL7 could be involved in inducing endothelial cell angiogenesis. Lastly and more recently, another RL11 gene family member, the UL10 gene, also has been reported to encode a soluble protein able to interfere with the activation, proliferation, and cytokine production of T cells (23).…”
mentioning
confidence: 98%